Analysis of Fault Zone Resonance Modes Recorded by a Dense Seismic Array Across the San Jacinto Fault Zone at Blackburn Saddle. Issue 10 (10th October 2020) - Qiu, Hongrui; Allam, Amir A.; Lin, Fan‐Chi; Ben‐Zion, Yehuda
Abstract: We present observations and modeling of spatial eigen‐functions of resonating waves within fault zone waveguide, using data recorded on a dense seismic array across the San Jacinto Fault Zone (SJFZ) in southern California. The array consists of 5‐Hz geophones that cross the SJFZ with ~10–30 m spacing at the Blackburn Saddle near the Hemet Stepover. Wavefield snapshots after the S wave arrival are consistent for more than 50 near‐fault events, suggesting that this pattern is controlled by the fault zone structure rather than source properties. Data from example event with high signal to noise ratio show three main frequency peaks at ~1.3, ~2.0, and ~2.8 Hz in the amplitude spectra of resonance waves averaged over stations near the fault. The data are modeled with analytical expressions for eigen‐functions of resonance waves in a low‐velocity layer (fault zone) between two quarter‐spaces. Using a grid search‐based method, we investigate the possible width of the waveguide, location within the array, and shear wave velocities of the media that fit well the resonance signal at ~1.3 Hz. The results indicate a ~300 m wide damaged fault zone layer with ~65% S wave velocity reduction compared to the host rock. The SW edge of the low‐velocity zone is near the mapped fault surface trace, indicating that the damage zone is asymmetrically located at the regionally faster NE crustal block. The imaging resolution of the fault zone structure can be improved by modeling fault zone resonance modes and trapped waves together. Key Points: Source‐independent resonance fault zone wavefield is consistently observed after S wave arrival in data recorded by a dense array A fault zone model with a low velocity layer between two quarter spaces can fit well the resonance wavefield at ~1.3 Hz Modeling the resonance wavefield provides independent constraints on fault zone properties complementary to previous studies